Liver stiffness measurement predicted liver‐related events and all‐cause mortality: A systematic review and nonlinear dose–response meta‐analysis - Wang, Junna; Li, Jiajun; Zhou, Quan; Zhang, Dandan; Bi, Qiu; Wu, Yulin; Huang, Wenxiang (Hepatology communications, 2018)
Numerous studies have investigated the prognosis value of the liver stiffness measurement (LSM) by transient elastography in assessing the risk of liver‐related events (LREs) and all‐cause mortality in patients with chronic liver disease (CLD). However, the shape of the dose–response relationship between them remains unclear. We searched PubMed, Embase, the Cochrane Library, and reference lists of articles for studies published up to July 1, 2017, that assessed the LSM in predicting LREs and all‐cause mortality among subjects with CLD. Fifty‐four observational cohort studies with 35,249 participants were included. Summary relative risks (RRs) were calculated using a random‐effects model, and a restricted cubic spline function was used to model the dose–response association. LREs and all‐cause mortality were increased in subjects with a high LSM (LRE: RR, 7.90; 95% confidence interval [CI], 5.65, 11.05; I2 = 71.6%; all‐cause mortality: RR, 4.15; 95% CI, 2.56, 6.72; I2 = 68.5%). For each unit increment of liver stiffness, the summary RR was 1.06 (95% CI, 1.06, 1.07; I2 = 74.6%) for LREs and 1.06 (95% CI, 1.04, 1.07; I2 = 55.7%) for all‐cause mortality. A positive relationship with a nonlinear trend for LSM with LREs and all‐cause mortality was examined by a dose–response meta‐analysis (P < 0.001). When stratified by etiology, a nonlinear association was also found in patients infected with hepatitis C virus and those coinfected with hepatitis C virus and human immunodeficiency virus. In contrast, there was no evidence of departure from linearity among patients with hepatitis B virus infection (Pnonlinearity = 0.072). Conclusion: LSM is useful in screening LREs and all‐cause mortality in patients with CLD. Further studies are warranted in assessing the application of LSM in monitoring the risk of LREs and all‐cause mortality in clinical practice. (Hepatology Communications 2018;2:467‐476) This review aims to consider the dose‐response association of liver stiffness measurement with liver‐related events and all‐cause mortality in patients with chronic liver disease, which might contribute to the routine clinical application of LSM in predicting LREs in the management of patients with CLD.